Capacity evaluation on Cu rolling tribological/electric contact pairs under various contact load and applied voltage. (October 2019) - Song, Chenfei; Liu, Zili; Hou, Xinbin; Wang, Li; Zhang, Yongzhen
The electric/tribological behaviors of Cu rolling pairs were studied under various contact load and applied voltage. The real-time data of friction coefficient and current were obtained synchronously, and their variation was analyzed. Under high contact load and high voltage, the degradation of electric/tribological contact could be expressed as the growth of friction coefficient and the aggravation of frictional/electrical fluctuation. The applied voltage played an important role in morphology change and surface oxidation. Low roughness surface and adhesion were observed on electric rolling surface mainly because of the Joule heating and the adhesion could induce the growth of high friction coefficient. Meanwhile, due to the tribo-oxidation and anodic oxidation, obvious but uneven O distribution was detected on the same surface and could disturb tribological/electric contact. The results may be beneficial for understanding the fundamental behaviors of novel rolling conducting rotary joint.